The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health ca mpaigns aim to control disease or deliver essential health services an d products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to targe t certain populations, or to accelerate progress towards coverage targ ets. The Root Cause Analysis and Rapid Evaluation, Action, and Learnin g toolkits present a systematic but flexible approach to identifying t he root causes of campaign bottlenecks and then designing, testing, an d refining solutions to optimize potential impact. These toolkits resp ond to a growing need for “fit-for-purpose” rapid-testing, adaptive le arning approaches to evaluation and the need for a culture shift towar d iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehens ive package of toolkits, in addition to the individual Root Cause Anal ysis toolkit and Rapid Evaluation, Action, and Learning toolkit are av ailable below.